Legal Review on Military Criminal Acts in Peaceful Time Done Repeatly According to the KUHPM and KUHP Based on Military Court Decision II-09 Bandung Number: PUT/067-K/PM-II-09/AD/III/2012 - Sufmi Dasco Ahmad (IHSA Institute, 2022)
This study aims to determine the military crime of dissertation based on the decision of the military court of Bandung City. The settlement process for desertion crimes committed by members of the Indonesian National Armed Forces basically includes the Military Court, the High Military Court, the Main Military Court, and the Military Combat Court (Article 31 of Law Number 31 of 1997). The Military Court, like other judicial bodies, also leads to the Supreme Court as the highest court in Indonesia. This research was taken with a descriptive method, meaning that it aims to describe in full the characteristics and circumstances, personal and group behavior by separating the data that has been collected according to their respective categories, to be interpreted in an effort to answer problems in writing. So the results of this study explain that, according to the Law of the Republic of Indonesia Number 25 of 2014 concerning Military Disciplinary Law, Article 8 CHAPTER V entitled Military Disciplinary Law and Military Disciplinary Punishment explains that several types of Military Disciplinary Punishment Violations have been published by the government Indonesia consists of all acts that are contrary to official orders, official regulations, or actions that are not in accordance with military rules and acts that violate criminal laws and regulations of such a light nature. In addition, judges at the Military Court are appointed and dismissed by the President as Head of State at the suggestion of the Commander in Chief and based on the approval of the Chief Justice of the Supreme Court. For this reason, before taking office, judges are required to take an oath or promise according to their respective religions. According to Article 23 of Law Number 31 of 1997, the power of the Military Court is to examine and decide at the first instance a criminal offense in which the defendant is a soldier with the rank of Captain and below, a member of a group or service or agency or who is equal or considered a soldier based on the law. The rank of Captain and below and a person who is not the same as a soldier or member of a group or service or agency that is not equal is not considered a soldier under the law which must be tried by the Military Court.